Modification of Cuttlefish Bone-Derived CaO Catalyst via SrO Impregnation for Optimizing the Conversion of Waste Cooking Oil into Biodiesel - Cut Rahmah Saputri; Muhammad Muhammad; Adi Setiawan (Reaktor, 2025)
This study investigates the utilization of waste cooking oil (WCO) as a biodiesel feedstock using a heterogeneous catalyst derived from cuttlefish bone. The catalyst was modified via Sr(NO₃)₂ impregnation at different composition ratios (98:2, 95:5, and 90:10 % w/v) to produce CaO–SrO catalysts, followed by chemical activation with NaOH (2, 4, and 6 g). Catalyst characterization was conducted using scanning electron microscopy coupled with energy-dispersive spectroscopy (SEM–EDS) and X-ray diffraction (XRD) to examine surface morphology, elemental distribution, and crystalline phases. The results indicate that the catalyst with a 90:10 CaO–SrO composition and 6 g NaOH activation (C90S10–N6) exhibited the most homogeneous surface morphology, uniform Sr dispersion, and enhanced phase stability. Transesterification of WCO under a methanol-to-oil molar ratio of 9:1, catalyst loading of 1 wt%, and reaction time of 2 h resulted in a biodiesel yield of 95.5%. The produced biodiesel showed a density of 0.87 g/mL, water content of 0.64%, calorific value of 38.52 MJ/kg, and a reduction in free fatty acid (FFA) content from 2.84% to 1.71%. These findings demonstrate that SrO-modified CaO catalysts derived from cuttlefish bone are effective, sustainable, and economically viable for enhancing biodiesel production from waste cooking oil.